MSCs on an acellular dermal matrix (ADM) sourced from neonatal mouse skin regulate collagen reconstruction of granulation tissue during adult cutaneous wound healing. Issue 37 (26th April 2017) - Chen, Maosheng; Jin, Ying; Han, Xue; Wang, Ning; Deng, Xiaoyuan; Liu, Hanping
Abstract : The novel strategy of MSCs seeded on ADM sourced from neonatal mouse skin promotes full-thickness cutaneous wound healing. Abstract : Full-thickness cutaneous wound repair in adults usually leads to non-regenerative healing, which produces disorganized and non-functional fibrotic tissues. Mesenchymal stem cells (MSCs) on acellular dermal matrix (ADM) scaffolds are currently believed to be a promising strategy for wound healing improvement. Extracellular matrix (ECM) is aware of playing a pivotal role in wound healing, and changing the properties of the ECM is therefore expected to alter repair outcomes. Inspired by the analogous regeneration process in foetal skin with minimal or no scar tissue formation, in this study, ADM scaffold sourced from 1 day old mouse skin is introduced. Its influence on collagen reconstruction of granulation tissue during adult full-thickness wound healing is revealed and is compared to that from 20 week old mouse skin. Advanced nonlinear optical two-photon fluorescence (TPF) and second-harmonic generation (SHG) imaging were used to intravitally and three-dimensionally monitor the activities of MSCs and formation of granulation tissue. Dynamic changes of collagen content in granulation tissue were analyzed from aspects of synthesis and degradation. The associated collagen proteins, type I and type III collagen (Col-I and Col-III) and matrix matalloproteinase-13 (Mmp-13) were assessed at the transcriptional, translational and deposition levels. The results showed that there were significant differences in remodelling characteristics as a consequence of ADM properties. One-day old ADM + MSC treatment induced up-regulation of Col-III expression, down-regulation of Col-I and also down-regulation of Mmp-13. Accordingly, 1 day ADM + MSC treatment caused higher type III collagen deposition and a higher ratio of Col-III/Col-I in the granulation tissue. ADM derived from 1 day old skin ECM was superior to ADM derived from 20 week old skin ECM, caused enhanced angiogenesis, down regulation of TGF-β1 and promoted re-epithelization and faster, more constructive, and compositionally appropriate formation of granulation tissue. These results suggest that ADM derived from 1 day old skin ECM is a favourable biomaterial for adult wound healing.